Study of the effect of bleaching agents on the crystalline index of cellulose-based materials derived from corn husk by CP/MAS 13C NMR and FT-IR spectroscopies - Huamani Palomino, Ronny G. (2024)
This work proposes an evaluation of the Crystalline Index (CrI) in function of the bleaching process employed during cellulose extraction from corn husk, for further characterization using CP/MAS 13C NMR, XRD, and FT-IR. In that sense, CrI values were calculated by FT-IR and the bands associated with the crystalline and amorphous regions were observed at 1424 cm−1 and 896 cm−1, respectively. Similarly, the signals due to ordered (89.1 ppm) and disordered (84.2 ppm) cellulose chains were detected by solid-state 13C NMR, while the Segal equation was only used for comparison purposes. Additionally, PCA studies showed consistent results attributed to the crystalline region in cellulose domains analyzed by both, FT-IR and solid-state 13C NMR. The results revealed the coexistence of cellulose I/cellulose II and its effect on CrI, as well as the incomplete mercerization process, in some cases non-cellulosic residues can cause an overestimation of CrI. Additionally, the thermal stability and the glass transition temperature were determined by TGA/DTA and DSC analyses. Finally, a partially fibrillated-network morphology with a diameter of 20.47 ± 2.77 μm was observed in cellulose bleached with peracetic acid, whereas organosolv method provides flexible and clean microfibrils with diameter sizes between 10 and 9 μm.